2022
DOI: 10.3389/fcell.2022.846864
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Insights Into the Biological Function and Clinical Significance of Long Noncoding RNA in Glioblastoma

Abstract: Glioblastoma (GBM) is one of the most prevalent and aggressive cancers worldwide. The overall survival period of GBM patients is only 15 months even with standard combination therapy. The absence of validated biomarkers for early diagnosis mainly accounts for worse clinical outcomes of GBM patients. Thus, there is an urgent requirement to characterize more biomarkers for the early diagnosis of GBM patients. In addition, the detailed molecular basis during GBM pathogenesis and oncogenesis is not fully understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 211 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…Due to their structural diversity, lncRNAs can interact with miRNAs, RNAs, or proteins to regulate downstream genes and signaling pathways [ 32 ]. Here, we confirmed that lncBIRC3-OT had a high affinity for RELA by RNA pull-down assay followed by LC-MS and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their structural diversity, lncRNAs can interact with miRNAs, RNAs, or proteins to regulate downstream genes and signaling pathways [ 32 ]. Here, we confirmed that lncBIRC3-OT had a high affinity for RELA by RNA pull-down assay followed by LC-MS and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…According to the complete genomic transcript, the percentage of lncRNAs is markedly higher than that of coding RNAs. lncRNAs were originally regarded as transcriptional noise, but subsequently, studies have shown that lncRNAs participate in various biological activities by interacting with DNA, RNA, and proteins through several mechanisms, such as genomic imprinting, chromosome modification, and telomere maintenance 8,9 . They are also associated with various human diseases, including tumors 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs were originally regarded as transcriptional noise, but subsequently, studies have shown that lncRNAs participate in various biological activities by interacting with DNA, RNA, and proteins through several mechanisms, such as genomic imprinting, chromosome modification, and telomere maintenance. 8 , 9 They are also associated with various human diseases, including tumors. 10 , 11 Nuclear enriched abundant transcript 1 (NEAT1) is an lncRNA with high expression in many diseases, including hepatocellular carcinoma, breast cancer, and nonalcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma (GBM) is one of the most prevalent and lethal solid tumors with an abysmal prognosis [ 1 ]. Despite recent advances in treating GBM, including surgery, chemotherapy, and radiation, the median survival time of GBM patients remains at only 15 months [ 2 , 3 ]. The worse prognosis and subsequent tumor relapse of GBM could be partially attributed to the tumorigenic potential of glioblastoma stem cells (GSCs).…”
Section: Introductionmentioning
confidence: 99%